PENGARUH KUALITAS PELAYANAN, REPUTASI, DAN KEPERCAYAAN PADA KESETIAAN NASABAH BANK DI SURAKARTA - Fitri Nur Handayani; Waluyo Budi Atmoko; Finisha Mahaestri Noor (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the Customer Loyalty that is influenced by Service Quality, Reputation and Trust. Customer loyalty is very important for the long-term sustainability of bank operations. However, the marketing efforts made by the bank's competitors make customers have the opportunity to move to another bank. Data obtained through online questionnaire which is distributed to banking customers. The sampling technique used was purposive sampling with a population of 200 respondents. Hypothesis testing is done by using SEM. The results of this study indicate that trust has no significant effect on customer satisfaction, reputation has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction, customer satisfaction has a significant effect on commitment, and commitment has a significant effect on customer loyalty.